Metal-insulator oscillations in a two-dimensional electron-hole system - Nicholas, R; Takashina, K; Lakrimi, M; Kardynal, B; Khym, S; Mason, N; Symons, D; Maude, D; Portal, J (2000)
The electrical transport properties of a bipolar InAs/GaSb system have been studied in a magnetic field. The resistivity oscillates between insulating and metallic behavior while the quantum Hall effect shows a digital character oscillating from 0 to 1 conductance quantum e(2)/h. The insulating behavior is attributed to the formation of a total energy gap in the system. A novel looped edge state picture is proposed associated with the appearance of a voltage between Hall probes which is symmetric on magnetic field reversal.